A new species of Xestophrys Redtenbacher, 1891 (Orthoptera: Tettigoniidae; Conocephalinae; Copiphorini) from West Bengal, India - Kumar, Hirdesh; Chand, D Suresh (Zootaxa, 2023)
A new species, Xestophrys bengalensis sp. nov., from the West Bengal state of India is described in this paper. The new species is superficially similar to the Indonesian species Xestophrys javanicus lombockensis Carl, 1908, but differs from the latter in the smaller size, anterior femur unarmed on the external margin, and hind femur with two spines on the internal margin. A key to the species of Xestophrys Redtenbacher, 1891 is also provided.